Avstro-ogrska diplomacija in vstop ZDA v vojno - Rahten, Andrej (Studia Historica Slovenica, 2018)
The article presents Croatian-Slovenian political relations in the Maribor electoral district in the Kingdom of Serbs, Croats and Slovenes, with focus on the agitation of Stjepan Radić and his allies. On the basis of sources from Maribor-based and other newspapers, the relationship between Radić's Croatian Peasant Party and the Slovenian People's Party, which was led by Anton Korošec, is shown in particular.
Keywords: Avstro-Ogrska; diplomacija; mednarodni odnosi; prva svetovna vojna; svetovna vojna 1914-1918; Združene države Amerike